الأخطاء في إستخدام النواسخ لدى طلبة المدارس الثانوية الدينية بولاية بهانج دار المعمور - Norillah 'Abdullah Hassim (al-Jami'ah al-Islamiyah al-'Alamiyah bi- Maliziya, 2005)
This study investigates the usage of Arabic language abrogators (alnawasih) among the students of the religious secondary schools in the State of Pahang by examining their syllabi and teaching methodology. Data collected for thus study were collected from Arabic learners in fifth and sixth grades from Sultan Abu Bakar Religious Secondary School, AlAttas Religious Secondary School and Tengku Ampuan Fatimah Religious Secondary School. The study discovers that the poor use of abrogators is not a major factor in the poor performance of Arabic learners. It was found that the poor performance is due to poor command of Arabic by teachers themselves. The problem is further compounded by ineffective curricula, syllabi and language environments. To remedy the problem, the study proposes a reevaluation of the Arabic language teaching curriculum and retraining of Arabic teachers.